Drying kinetics and product quality of green soybean under different microwave drying methods - Cao, X.; Zhang, M.; Fang, Zhongxiang; Mujumdar, A.; Jiang, H.; Qian, H.; Ai, H. (Taylor and Francis Inc, 2017)
The objective of this study was to investigate the effect of different microwave drying techniques on the drying kinetics and product quality of dried green soybean. Experiments were conducted using microwave vacuum drying (MVD), pulse-spouted vacuum microwave drying (PSMVD), pulse-spouted microwave drying (PSMD), and microwave freeze drying (MFD). Parameters of apparent density, color, processing temperature, expansion ratio, rehydration ratio, texture, and microstructure of the dried products were determined. The results showed that the MFD green soybean had a small change on bright color, compared with the fresh samples, but the drying time was the longest among the four methods. The bright color value of PSMVD/PSMD/MVD, respectively, was 79.77, 71.43, and 55.45, and drying time of them was slightly different. The PSMVD/PSMD showed advantages over MVD by improving the product quality.